Spatially high-resolved monitoring and risk assessment of polycyclic aromatic hydrocarbons in an industrial city - Nguyen, Tuyet Nam Thi; Kwon, Hye-Ok; Lammel, Gerhard; Jung, Kun-Sik; Lee, Sang-Jin; Choi, Sung-Deuk (Journal of hazardous materials, 2020)
Polycyclic aromatic hydrocarbons (PAHs) were monitored at 20 sites in semi-rural, urban, and industrial areas of Ulsan, the largest industrial city in South Korea, for one year. The target compounds were the 16 priority PAHs designated by the US Environmental Protection Agency except for naphthalene, acenaphthene, and acenaphthylene. Gaseous PAHs collected using polyurethane foam-based passive air samplers (PUF-PASs) and particulate PAHs predicted using gas/particle partitioning models were used to estimate the human health risks. The mean total cancer risk through inhalation intake and dermal absorption for all target age groups (children, adolescents, adults, and lifetime) ranged from 0.10 × 10-7 to 2.62 × 10-7, lower than the acceptable risk level (10-6), thus representing a safe level for residents. The cancer risk through dermal absorption and inhalation intake was predicted to be highest in winter, mostly due to the higher concentrations of PAHs, especially high-molecular-weight species with greater toxicity. Additionally, gaseous and particulate PAHs contributed more to dermal absorption and inhalation intake, respectively. As a consequence of local emissions and advection, the risks were higher in the industrial and semi-rural areas. This study suggests that human health risks can be cost-effectively mapped on a local scale using passive air sampling.
Keywords: Ulsan; gas/particle partitioning model; Risk assessment; PAS; PAHs